2018
DOI: 10.1051/matecconf/201819201029
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on dimensional accuracy of EDM deep hole using multi-hole interior flushing electrode

Abstract: Improper flushing of dielectric fluid adversely affects the dimensional accuracy produced in EDM deep hole process. This paper investigates the dimensional accuracy (e.g. roundness error and gap clearance) in EDM deep hole process of AISI P20 tool steel. The inner flushing electrode is newly proposed in this study, using the multi-hole interior flushing technique coupled with electrode rotation. The results showed that the multi-hole interior flushing with electrode rotation improves the deviation of roundness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Therefore, many researchers have studied how to improve the deep hole machining process. However, poor machining performance based on the removal of debris material, surface quality, and machining accuracy usually occurs in deep hole drilling due to the difficulties in gap cleaning and debris removal from the sparking area [34][35][36]. This leads to low production efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many researchers have studied how to improve the deep hole machining process. However, poor machining performance based on the removal of debris material, surface quality, and machining accuracy usually occurs in deep hole drilling due to the difficulties in gap cleaning and debris removal from the sparking area [34][35][36]. This leads to low production efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed that the enhanced flushing of debris from the machining gap increases machining performance. Chuvaree et al [34,43] investigated the dimension accuracy of an EDM deep hole using a multihole interior flushing electrode. They reported that the improved flushing technique is able to achieve a better closed gap tolerance and higher material removal rate compared with the conventional flushing method.…”
Section: Introductionmentioning
confidence: 99%
“…The copper electrode diameter was determined by the 3D handy scanner, and the EDM deep hole diameter was determined by the noncontact laser scanning confocal microscope. To determine distortion, the GC was measured at six locations (1,10,20,30,40, and 50 mm) in the machining direction, as shown in Figure 3. The maximum distortion of the six locations was used as the GC of a given EDM specimen because the maximum distortion reflects the effect of the disproportionate depth-to-diameter ratio (i.e., >4).…”
Section: Experimental Materials and Setupmentioning
confidence: 99%
“…The CCD generated 31 machining conditions, consisting of 16 factorial points, 7 center points, and 8 axial points. The EDM parameters and corresponding parametric values were based on previous studies on EDM using modified copper electrodes [4,30,31]. In this research, the workpiece and electrode were weighed before and after the deep hole machining with 0.001-g precision scale.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation